2019
DOI: 10.1038/s41371-019-0211-1
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen therapy in premature low birth weight infants is associated with capillary loss and increases in blood pressure: a pilot study

Abstract: Low birth weight (LBW) and premature birth are known risk factors for future cardiovascular disease and in particular essential hypertension (EH). Capillary rarefaction (CR) is an established hallmark of EH and is known to occur in individuals with a history of LBW. We previously reported that LBW infants do not have CR at birth but rather increased capillary density (CD). We hypothesized that LBW infants undergo a process of accelerated CR in early life, triggered in part by oxygen therapy. We studied 26 LBW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Continuing to explore the etiology of hypertension, especially in adolescence and childhood, has significant implications for preventing disease progression and improving global health. Low body weight, an indicator of congenital development dysplasia or an adverse intrauterine environment, has recently been thought to be widely implicated in high blood pressure and other cardiovascular diseases [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Continuing to explore the etiology of hypertension, especially in adolescence and childhood, has significant implications for preventing disease progression and improving global health. Low body weight, an indicator of congenital development dysplasia or an adverse intrauterine environment, has recently been thought to be widely implicated in high blood pressure and other cardiovascular diseases [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is a process as early-accelerated capillary remodeling that cause fast change in high capillary density at birth to capillary rarefaction in the next month and to intensify by oxygen therapy in the early of neonatal period. [ 5 24 26 ] Several studies believe that the vascular endothelial dysfunction is a key role in the causation of EH in LBW. [ 13 ] Furthermore, some studies believe that the serum concentration of uric acid could be an important factor in the pathogenesis of EH.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of LBW has been estimated between 15% and 20% of all births worldwide; in other words, it is more than 20 million births a year. Some epidemiologic studies have reported an increased risk of childhood-onset EH in LBW infants,[ 3 4 ] possibly due to alterations in their renal or vascular[ 5 6 7 ] systems related to reduced growth in utero , while others reported that high birth weight (BW), which may have long-term adverse metabolic effects, including insulin resistance[ 8 9 10 11 ] is also a risk factor for the development of EH in childhood. [ 5 9 10 ] The aim of this meta-analysis was to study the role of LBW on EH in children by analyzing the existing published literature.…”
Section: Introductionmentioning
confidence: 99%